Chapter 8. Conservation planning - Santos, Jorge (Septentrio Educational, 2015)
This chapter of CONΣERV IT deals with the following questions in aquatic conservation:- How do we express the suitability of habitat for different organisms and communities?- How to make spatial planning of conservation networks that takes into account multiple ecological and social criteria?- How to perform an economic analysis of the non-monetized conservation effects?Conservation Los Cayos Reserve short version